Dietary quercetagetin attenuates H2O2-induced oxidative damage and preserves meat quality in broilers by modulating redox status and Nrf2/ferroptosis signaling pathway - Hu, Wenyue; Liang, Huiqing; Zhao, Pengyu; Feng, Sijia; Li, Yuhan; Wu, Fengyang; Han, Shuaijuan (Frontiers in Veterinary Science, 2025)
In modern poultry production, oxidative stress has emerged as a pivotal factor compromising the health status and overall performance of broiler. The aim of this study was to investigate the effects of dietary quercetagetin (QG) supplementation on hydrogen peroxide (H2O2)-induced oxidative damage in breast muscle of broilers, focusing on growth performance, meat quality, and antioxidant function, and elucidating the underlying mechanisms. Two hundred and forty one-day-old Cobb broilers were randomly divided into three treatment groups: the control group, the H2O2 group and the H2O2 + QG group. The control and H2O2 groups were fed a basal diet, and the QG group was fed a basal diet supplemented with 100 mg/kg QG. The control group was intraperitoneally injected with normal saline, and the other two groups were treated with the same volume of 10% H2O2 solution on day 37. The experimental period was 42 days. The results showed that H2O2-induced oxidative stress increased the levels of drip loss, cooking loss, reactive oxygen species (ROS), and oxidation products in the breast muscle, and damaged the mitochondrial function. Compared with the control group, the mRNA expressions of glutathione peroxidase (GSH-Px), NAD(P)H quinone dehydrogenase 1 (NQO1), catalase (CAT), nuclear factor erythroid 2-related factor 2 (Nrf2), transferrin receptor protein 1 (TFR1), and ferritin heavy chain 1 (FTH1) in the breast muscle were decreased (p < 0.05). The addition of QG to the diet reduced the levels of ROS and oxidation products (p < 0.05). Meanwhile, the addition of QG to the diet increased the mRNA expressions of Nrf2 and TFR1, showing no significant difference from those of the control group. In conclusion, H2O2-induced oxidative stress impairs breast muscle quality, mitochondrial function, and antioxidant capacity in broilers. Dietary QG alleviates oxidative stress and improves meat quality by regulating the Nrf2 signaling pathway and ferroptosis-related mechanisms. This mechanism-based finding supports QG as a safe and effective dietary additive for broiler production, providing a practical solution to enhance animal health, stabilize meat quality, and promote the sustainability of intensive poultry farming.